2009
DOI: 10.1177/104063870902100413
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes, Antibiogram, and Pulsed-Field Gel Electrophoresis Profiles of Escherichia Coli Strains from Piglets in Korea

Abstract: Abstract. Adherence factors and enterotoxins are major virulence factors of enterotoxigenic Escherichia coli (ETEC). Antibiotics have been used frequently for the treatment and prevention of ETEC infection in piggeries worldwide, including Korea. Therefore, data on both virulence profiles and antibiotic resistance patterns are useful in the epidemiological study of ETEC. A total number of 198 E. coli field isolates were examined. The most prevalent pathotype was F1, followed by a combination of F1 and EAST1. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…In this study, all VTEC isolated were multidrug-resistant, in which high resistance rates were observed for Amp, Aml, Cip, Enr, Tet, Sxt, Chl and Nal (Figure 1). This is similar to recent reports from Thailand and Korea [15,26]. This suggests that the swine farms in those countries may have used the similar antimicrobials for prophylactics as the swine farms in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, all VTEC isolated were multidrug-resistant, in which high resistance rates were observed for Amp, Aml, Cip, Enr, Tet, Sxt, Chl and Nal (Figure 1). This is similar to recent reports from Thailand and Korea [15,26]. This suggests that the swine farms in those countries may have used the similar antimicrobials for prophylactics as the swine farms in Malaysia.…”
Section: Discussionsupporting
confidence: 89%
“…A study performed in Korea showed how E. coli strains isolated from diarrhoeic pigs were multi-resistant (resistant to more than 4 antibiotics) with high levels of resistance to several antibiotics: gentamicin (77%), trimethoprim-sulphametoxazole (75.7%), amoxicillin (75.7%), ampicillin (73%) and enrofloxacin (64.9%) [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies of antimicrobial resistance in Enterobacteriaceae isolated from farm animals, we identified some important antimicrobial resistance genes associated with transferable plasmids of similar sizes. In addition to antibiotic resistance genes, plasmids may also bear important toxin genes that could be maintained and disseminated to a wide range of microbes, especially members of the Enterobacteriaceae, from farm animals that share common environmental niches (9,10,13,15).…”
mentioning
confidence: 99%